Susceptibility to diamides differs in the field populations of Plutella xylostella and Spodoptera litura feeding on cole crops - Elakkiya, K.; Murugan, M.; Krishnamoorthy, S.V.; Senthil, N.; Vijayalakshmi, D. (Journal of Asia-Pacific entomology, 2024)
[Display omitted] •P. xylostella showed high diamide resistance, while S. litura remained susceptible.•Cross-resistance to flubendiamide and chlorantraniliprole was observed in both pests.•S. litura had higher baseline levels of detoxifying enzyme levels, but only GST was overexpressed in P. xylostella post-diamide exposure.•Oligophagy in P. xylostella fosters resistance, while polyphagy in S. litura reduces its resistance development. Diamides, a new class of insecticides, have been used in Indian agriculture for more than 15 years. The severe incidence of diamondback moth (DBM), Plutella xylostella L., and leafworm, Spodoptera litura Fab. on cabbage/cauliflower drew intensive applications of diamides in Southern India. The former is an oligophagous (specialist), while the latter is a polyphagous (generalist) pest. In India, DBM resistance to diamides has surfaced, but not for S. litura. The field populations collected from cauliflower and cabbage in Tamil Nadu’s various agro-climatic zones were tested for diamides resistance, viz., flubendiamide and chlorantraniliprole. The results revealed high resistance to flubendiamide and chlorantraniliprole in DBM field populations (98.32 to 54.52 mg/L, respectively) but not in S. litura (4.84 to 0.84 mg/L). Resistance fold in both pests were high for chlorantraniliprole rather than flubendiamide, and the KRI population stood top in resistance. The Resistance folds to flubendiamide (121.38) and chlorantraniliprole (227.16) got multi-folded for DBM when matched against reference susceptible population (SUS-I). Analysis of detoxifying enzymes (MFO, GST, CarE) in highly resistant DBM populations after sub lethal diamide exposures showed GST over-expression for up to 24 h, while none of the tested enzymes consistently expressed in S. litura. Further, there was a point mutation at the ryanodine receptor binding site (G4946E) in P. xylostella, which was absent in S. litura. Oligophagy seems to favour resistance build-up in DBM, while polyphagy downplays resistance development in S. litura. Populations of DBM may require effective resistance management intervention to address metabolic detoxification and point mutation.